As vozes da infância ribeirinha na transformação da prática pedagógica da educação infantil - Soares, Maria das Graças Pereira (2017)
The research had the aim to investigate how the riverside childhood voices, considering their sociocultural experiences, knowledge, and curiosities may transform the pedagogical practice experienced in the Early Childhood Education from a public school located in the community called Paraná do Espírito Santo de Cima in the city of Parintins (AM). The investigation problem is: How the riverside childhood voices may transform the pedagogical practice in the Early Childhood Education? Therefore, a qualitative research was conducted with an ethnographic case study in order to describe and to analyze the school context, focusing on the process involved in the pedagogical practice of a mixed grade class from the Early Childhood Education. It was made at the same time a field research and a theoretical research based on the Paulo Freire Pedagogy and authors as Ariès (1981), Arroyo (1999, 2006, 2009, 2013), Brandão (2014), Charlot (2013), Faria (2002, 2009, 2011, 2012), Hage (2005), Kramer (1995, 2002, 2006, 2011, 2015, 2016), Santomé (2013), Saul and Silva (2009, 2014) and Saul and Saul (2013). The methodological procedures used to collect the data were the document analysis, the direct observation of the pedagogical practice, semistructured interviews with the teachers and the parents and dialog with the children (4 to 5 years old). The results showed that the riverside children voices bring knowledge, opinions, interests, and curiosities and that they are useful tools for the teachers understand the childhood universe. The dialog in the rounds of conversation and the multiple languages in the pedagogical practices are ways through which the children may express themselves. However, the investigated school must build/rebuild its curricular proposal including all the subjects involved in the education process in the view of a pedagogical practice in which the children, the educational process center, may problematize and analyze issues related to their lives and their environment